The thief of always ebook - Barker, Clive (2014)
The horror story your students have been asking you for! The only children's story by the master of horror. Mr Hood's Holiday House has stood for a thousand years, welcoming countless children into its embrace. It is a place of miracles, a blissful round of treats and seasons, where every childish whim may be satisfied. There is a price to be paid, of course, but young Harvey Swick, bored with his life and beguiled by Mr Hood's wonders, does not stop to discover the consequences. It is only when the House shows its darker face – when Harvey discovers the pitiful creatures that dwell in its shadow – that he comes to doubt Mr Hood's philanthropy. The house and its mysterious architect are not about to release their captive without a battle, however. Mr Hood has ambitions for his new guest, for Harvey's soul burns brighter than any soul he has encountered for a thousand years...